Emerging trends in applications and infrastructures for computational biology, bioinformatics, and systems biology : systems and applications - Tran, Quoc-Nam; Arabnia, Hamid (Emerging trends in computer science & applied computing., 2016)
"Emerging Trends in Computational Biology, Bioinformatics, and Systems Biology discusses the latest developments in all aspects of computational biology, bioinformatics, and systems biology and the application of data-analytics and algorithms, mathematical modeling, and simu- lation techniques"--